Além do ofício: narrativas de D.Severina (Gorda) e D.josefa (Zefinha), rezadeiras de Itabaina, PB - Nascimento, Danielle Gomes do (2017)
This research aims to present the relations between discourse and cultural manifestations, evidencing oral practices as an instigator of the experiences and knowledge acquired by the subjects throughout life. The work aims to present and analyze, from the memories of the mourners, the narratives that make up the office and other knowledge. Two Itamarian mourners were chosen; D. Josefa Maria da Silva, known in the community by D. Zefinha and D. Severina Maria da Conceição, known as D. Gorda. These women were given a voice that, through their narratives, could talk about what they lived and learned, highlighting the experiences and knowledge transmitted orally. The voice in the narratives is accompanied by different supports - memory, body, sensations and feelings, elements that give the voice poetic character and generate senses. In addition to the craft of prayer, they also learned other oral domains: singing, short story, drama and poetry. As for the methodology, the ethnographic method was used, which values and respects Orality and the knowledge shared by the culture, as well as promoting the interaction between the collaborators and the researcher. Method also necessary for the meeting of oral documents (recorded interviews, notes in the field book during informal conversations), whose basis is (2003,2015). For the analysis and interpretation of data, Zumthor (1993, 2010), Ong (1998), Certeau (2014), Bakhtin (2003), Fernandes (1972) and others are used for evidencing Orality in popular contexts and understanding voice as a poetic act. One can see that the variety of knowledge was acquired in daily life in different ways: seeing, hearing, repeating and experiencing.The narratives were brought to the fore by memory, allowing voices of the past and present to meet and walk side by side for a few moments, instigating reflections and evaluations of themselves and their lives, as well as making known "the unknown" - the mode how cultural practices are organized and rooted in the community. It was also verified that the voice circulates in a variable way and is conducted by subjects that update it, transforming and recreating from their needs and spaces of coexistence.